1997
DOI: 10.1002/pen.11657
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of CaCO3 particulate‐filled β‐crystalline phase polypropylene composites

Abstract: β‐crystalline phase polypropylene (PP) composites containing 5, 10, 20, 30, and 40% (by weight) of CaCO3 filler were prepared by injection molding. The β‐form PP was produced by adding a bicomponent β‐nucleator consisting of equal amounts of pimelic acid and calcium stearate. The morphology, static tensile, and impact properties of these composites were investigated in this study. Scanning electron microscopy (SEM) observations revealed that the β‐spherulites of the polymer matrix of the composites exhibit cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 25 publications
2
62
0
Order By: Relevance
“…Calcium carbonate is among the most common particulate filler added to iPP in order to reduce its cost and improve its rigidity, although reduction of ductility and toughness is usually observed. Tjong et al [1] analyzed iPP composites having up to 40% of CaCO 3 and concluded that a drop in impact resistance and yield strength with increasing filler content is due to a decrease in the concentration of the tougher polymer matrix, an increase in the amount of the weaker filler/matrix interface, and to the debonding of the filler from the polymer matrix. Premphet & Horanont [2] demonstrated that up to 10% in volume of surface treated CaCO 3 , iPP composites may exhibit higher impact strength, however, concomitantly, a significant reduction in the tensile yield strength.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Calcium carbonate is among the most common particulate filler added to iPP in order to reduce its cost and improve its rigidity, although reduction of ductility and toughness is usually observed. Tjong et al [1] analyzed iPP composites having up to 40% of CaCO 3 and concluded that a drop in impact resistance and yield strength with increasing filler content is due to a decrease in the concentration of the tougher polymer matrix, an increase in the amount of the weaker filler/matrix interface, and to the debonding of the filler from the polymer matrix. Premphet & Horanont [2] demonstrated that up to 10% in volume of surface treated CaCO 3 , iPP composites may exhibit higher impact strength, however, concomitantly, a significant reduction in the tensile yield strength.…”
Section: Introductionmentioning
confidence: 99%
“…Premphet & Horanont [2] demonstrated that up to 10% in volume of surface treated CaCO 3 , iPP composites may exhibit higher impact strength, however, concomitantly, a significant reduction in the tensile yield strength. Many researchers [1][2][3][4][5][6][7] have studied the toughening of iPP with CaCO 3 , so the improvement of the impact strength followed by the reduction of yield strength, flexural strength and modulus of the composites are the ordinary outcome. It was also observed, that among different types of calcium carbonate particles, those which were surface treated and submicron sized gave composites with superior combination of mechanical properties [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium carbonate is used frequently in plastic sector. This material which is used to increase colour property and quality of dyeing is often seem in nature [10,11]. In this study, calcium carbonate, bentonite, and kaolin clay were mixed with Low Density Polyethylene (LDPE) material in certain mass ratio, and composite materials are made.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, high specific surface area of the fillers is expected to enhance interphase effects and tensile strength of the PP [1]. For this purpose, different types of reinforcing agents have been used, such as CaCO 3 [2], talc [3], mica [4], and glass fiber [5].…”
Section: Introductionmentioning
confidence: 99%